Blood pressure and renal injury in dogs with visceral leishmaniasis - Sousa, Marlos G.; Lima, Amanda B.G.; Araújo, Cristiane R.A.; Silva, Vinícius B.C.; Ramos, Adriano T.; Machado, Gisele F. [UNESP]; Melo, Guilherme D. [UNESP]; Carareto, Roberta (FapUNIFESP (SciELO), 2016)
Systemic hypertension is known to be a common consequence of chronic renal disease, which is frequently diagnosed in dogs with visceral leishmaniasis. Although many veterinary investigations have looked at the renal injury caused by Leishmania spp., the role played by this complication in the development of arterial hypertension documented in some animals with visceral leishmaniasis is not completely understood. In this study, 18 adult dogs with naturally-occurring visceral leishmaniasis and varying clinical signs underwent an indirect blood pressure measurement. Also, sera and spot urine were used for laboratory tests. The median systolic blood pressure was 135.2mmHg (95% confidence interval: 128.5-147.7), median mean arterial pressure was 105.8mmHg (98.3-110.4), and median diastolic arterial pressure was 88.5mmHg (77.8-92.5). No differences existed between asymptomatic and symptomatic animals regarding arterial pressure, and no correlations were documented between blood pressure and serum creatinine, blood urea, urine protein-to-creatinine ratio, urine specific gravity, and the fractional excretion of sodium and potassium. Although an association between hypertension and the identification of inflammation on histopathology could not be demonstrated in hypertensive animals, the assessment of kidney samples from 12 dogs indicated mild inflammation with a lymphoplasmacytic infiltrate (6/12), moderate inflammation with multifocal lymphoplasmacytic and histiocytic infiltrates (3/12), and multifocal degeneration and protein casts (2/12). Anti-Leishmania spp. immunohistochemistry assays stained the renal epithelium in 2/12 of the animals. Even though mild systemic hypertension was documented in a small subset of animals, no relationship between the severity of clinical signs and hypertension could be anticipated.
Keywords: Blood pressure; Dog; Glomerulopathy; Hypertension; Kidney; Leishmaniasis; Parasitic disease; Proteinuria